2012
DOI: 10.1109/tbcas.2011.2175390
|View full text |Cite
|
Sign up to set email alerts
|

Inductive and Ultrasonic Multi-Tier Interface for Low-Power, Deeply Implantable Medical Devices

Abstract: We report the development of a novel multi-tier interface which enables the wireless, noninvasive transfer of sufficient amounts of power as well as the collection and transmission of data from low-power, deeply implantable analog sensors. The interface consists of an inductive coupling subsystem and an ultrasonic subsystem. The designed and experimentally verified inductive subsystem ensures that 5 W of power is transferred across 10 mm of air gap between a single pair of PCB spiral coils with an efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Denisov and Yeatman (2010) performed a comparison between near-field inductive and acoustic power transfer concluding that near-field inductive power transfer is more efficient for larger devices with shallower tissue depths while acoustic power transfer is more efficient for smaller devices with deeper tissue depths. Sanni et al (2012) and Seo et al (2013) proposed hybrid systems where a larger inductive power transfer system transmitted power through skin and/or bone to a smaller in vivo acoustic plate-to-plate system. It is notable that the plate diameters of interest are, for the most part, decreasing with time.…”
Section: Introductionmentioning
confidence: 99%
“…Denisov and Yeatman (2010) performed a comparison between near-field inductive and acoustic power transfer concluding that near-field inductive power transfer is more efficient for larger devices with shallower tissue depths while acoustic power transfer is more efficient for smaller devices with deeper tissue depths. Sanni et al (2012) and Seo et al (2013) proposed hybrid systems where a larger inductive power transfer system transmitted power through skin and/or bone to a smaller in vivo acoustic plate-to-plate system. It is notable that the plate diameters of interest are, for the most part, decreasing with time.…”
Section: Introductionmentioning
confidence: 99%
“…The power harvesting using piezoelectric materials is a solution for self-powered implantable systems [3]. However, the power harvesting from vibration is sensitive 978-1-4673-4642-9/13/$31.00 ©2013 IEEE [7], [8], [9].…”
Section: Available Power Sources For Implantable Biomedical Systemsmentioning
confidence: 99%
“…Therefore, the transmitter output power level increases up to a few watts. Ultrasound is a suitable option for power transfer to deeply implants in the body [8]. The power transfer efficiency of ultrasound systems is very high in the water but not in the air.…”
Section: Available Power Sources For Implantable Biomedical Systemsmentioning
confidence: 99%
“…In addition, unlike RF transmission, which is regulated according to FCC requirements, ultrasonic power delivery and transmission is only limited by the structure's mechanical compliance. In literature, several ultrasonic telemetry systems have been reported for use in metallic structures [21]- [23] and for in vivo applications [24]. In [15]- [20], passive ultrasonic telemetry systems have also been reported that eliminate the need for batteries on the sensors.…”
Section: Introductionmentioning
confidence: 99%